Relasi Sosial Umat Kong Hu Cu Di Kawasan Simpang Lima Ampenan Kota Mataram - Lutfatul Azizah; Yuhana Yuhana (UIN Mataram, 2022)
This article aims to looks at the pattern of the relations built by the Confucians community and the practices of peace that are applied. As a minority religious group, The Confucians community in Ampenan cannot be separated from their efforts to survive with the adaptation strategies that are carried out. The intended adaptation strategy is the pattern of relationships that are built. Using a qualitative research method where the data collection process uses the method of observation, interviews and documentation. With the help of AGIL theory, this article also finds that the adaptation made by the Confucians is an merely an adaptation to the economic activity’s as an primary aspect. The practice of peace that is applied is also with the economic aspect. This partially refutes AGIL's theoretical framework by looking at Goal Attainment, the integration and built latency do not reach their ideal point. The main reason why the Confucians chose the economic aspect over the religious aspect was to evade the unsuccesful story between Hindu-Muslims which failed to build the relationship pattern through the pattern of marriage relation.s The effective pattern of relations in maintaining the harmony of the people in the Simpang Lima Ampenan Mataram area is through the economical aspect